Mechanochemically aminated multilayer graphene for carbon/polypropylene graft polymers and nanocomposites - L. Burk; M. Walter; A. C. Asmacher; M. Gliem; M. Moseler; R. Muelhaupt (eXPRESS Polymer Letters, 2019)
The two-stage mechanochemical amination of graphite by dry ball milling of graphite in a planetary ball mill under Ar followed by NH3 yields aminated multilayer graphene (AMFG) as intermediates for carbon/polymer hybrids and nanocomposites. Opposite to efficient edge-selective graphene functionalization under Ar, CO2 and N2 pressure, the onestage ball milling under NH3 pressure affords rather low N content (<0.5 wt%) and fails to reduce the graphite platelet size. According to DFT (Density Functional Theory) calculations NH3 exhibits low mobility between graphene layers and forms weak bonds to carbon which impair breakage of carbon bonds. In the two-stage ball-milling of graphite under Ar affords reactive carbon nanoparticles which react with NH3 in the second stage. With increasing milling duration of the second stage the nitrogen content increases to 3.2 wt%. As verified by XPS (X-ray photoelectron spectroscopy) measurements primary amine groups are formed which couple with various dicarboxylic anhydride groups including maleated PP to produce imidefunctionalized graphene. This is of interest to produce compatibilizers and dispersing agents for carbon/PP nanocomposites exhibiting improved mechanical properties. Two-stage mechanochemistry holds promise for carbon nanoparticle functionalization well beyond amination.